2011
DOI: 10.1016/j.adolescence.2011.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Brief report: Gum chewing affects standardized math scores in adolescents

Abstract: Gum chewing has been shown to improve cognitive performance in adults; however, gum chewing has not been evaluated in children. This study examined the effects of gum chewing on standardized test scores and class grades of eighth grade math students. Math classes were randomized to a gum chewing (GC) condition that provided students with gum during class and testing, or a control condition with no gum (NGC). Participants included 108 students. The math sections of the Texas Assessment of Knowledge and Skills (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 12 publications
1
13
0
Order By: Relevance
“…The two experiments in the present study replicate and extend previous research on chewing gum, by demonstrating chewing gum during a period of self‐study enhances subsequent test performance, consistent with the findings of Allen et al () and Johnston et al (). Results of Experiment 2, but not Experiment 1, indicated chewing gum enhanced alertness during the self‐study period, consistent with the findings of a number of previous studies (e.g., Hirano & Onozuka, ; Johnson et al, ; Morgan et al, ; Sakamoto et al, ; Smith, ; Stephens & Tunney, ; Smith, ; Tucha et al, ; Tucha & Simpson, ).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The two experiments in the present study replicate and extend previous research on chewing gum, by demonstrating chewing gum during a period of self‐study enhances subsequent test performance, consistent with the findings of Allen et al () and Johnston et al (). Results of Experiment 2, but not Experiment 1, indicated chewing gum enhanced alertness during the self‐study period, consistent with the findings of a number of previous studies (e.g., Hirano & Onozuka, ; Johnson et al, ; Morgan et al, ; Sakamoto et al, ; Smith, ; Stephens & Tunney, ; Smith, ; Tucha et al, ; Tucha & Simpson, ).…”
Section: Discussionsupporting
confidence: 91%
“…They also found chewing gum students completed more work than nonchewing gum students. Johnston, Tyler, Stansberry, Moreno, and Foreyt () conducted a longer study (14 weeks) to investigate the effects of chewing gum on standardised math test scores of adolescent students. Students in the gum chewing condition “had a significantly greater increase in … math scores compared to … the non‐chewing gum condition” (Johnston et al, , p.458).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also noteworthy that sugar-free gum has more health claims approved by the European Food Safety Authority than any other food category. 55 52 These results were confirmed in a study of restrained eaters where chewing gum was found to reduce snack intake by about 10%; hunger and the desire to eat also were suppressed significantly.…”
Section: The Role Of Chewing Gummentioning
confidence: 58%
“…However, in order to enhance exam success, one needs to start chewing gum at least 14 days before the exam. Johnston, Tyler, Stansberry, Morene, and Foreyt () found that students in the chewing gum group improved their standardized test scores and maintained higher grades in mathematics (14 weeks) than those in the no‐chewing gum group. Smith and Woods () determined that chewing gum was also associated with a decrease in the failure to get enough academic work done.…”
Section: Discussionmentioning
confidence: 99%